An In Vitro Comparison of Fracture Load of Zirconia Custom Abutments with Internal Connection and Different Angulations and Thickness: Part I. Issue 4 (13th January 2014) - Albosefi, Abdalah; Finkelman, Matthew; Zandparsa, Roya
Abstract Purpose The purpose of this in vitro study was to compare the fracture load of one‐piece zirconia custom abutments with different thicknesses and angulations. Materials and Methods Forty zirconia custom abutments were divided into four groups. Group A‐1 and group B‐1 simulated a clinical situation with an ideal implant position, which allows for the use of straight zirconia custom abutments with two thicknesses (0.7 and 1 mm). Groups A‐2 and B‐2 simulated a situation with a compromised implant position requiring 15° angulated abutments with different thicknesses (0.7 and 1 mm). Implant replicas were mounted in self‐cure acrylic jigs to support the abutments in all groups. The zirconia custom abutments were engaged in the implant replicas using a manual torque wrench. Each jig was secured and mounted in a metallic vice 30° relative to a mechanical indenter. All groups were subjected to shear stress until failure using a universal testing machine with a 0.5 mm/min crosshead speed with the force transferred to the lingual surface of the zirconia custom abutments 2 mm below the top surface. The universal testing machine was controlled via a computer software system that also completed the stress‐strain diagram and recorded the breaking fracture load. The fracture loads were recorded for comparison among the groups and subjected to statistical analysis (two‐way ANOVA). Results The mean fracture load of zirconia custom abutments across the groups (A‐1 through B‐2) ranged from 160 ± 60 to 230 ± 95 N. The straight zirconia custom abutment exhibited the highest fracture load among the groups (p = 0.009); however, the thickness of the zirconia custom abutment had no influence on the strength of any of the specimens (p = 0.827). Conclusions There was no statistically significant difference in fracture strength between the 0.7 and 1.0 mm groups; however, angulated zirconia custom abutments had the lowest fracture load. Clinical Implication The results of this in vitro study will help dental practitioners with their decision‐making process in selecting the type of custom abutment to be used clinically.